Pneumococcal disease during Hajj and Umrah: Research agenda for evidence-based vaccination policy for these events. Issue 29 (May 2019) - Yezli, Saber; van der Linden, Mark; Booy, Robert; AlOtaibi, Badriah
Abstract: Pneumococcal disease is an important cause of morbidity and mortality worldwide with a significant financial burden. Pneumococcal vaccines are available and recommended in many countries for at-risk populations including young children, the elderly and those with underlying medical conditions. The Hajj and Umrah mass gatherings attract millions of Muslim pilgrims to the Kingdom of Saudi Arabia each year. These events increase the risk of pneumococcal disease especially among the large number of elderly pilgrims with co-morbidities. However, there is no unified official policy for vaccination against pneumococcal disease for pilgrims attending Hajj and Umrah, largely due to the lack of a strong evidence-base in the context of these events. Here we review knowledge gaps regarding pneumococcal disease during Hajj and Umrah and highlight important research agendas to strengthen the evidence-base to inform pneumococcal vaccination policy for pilgrims. Available data indicates that the true clinical and financial burdens of pneumococcal disease at Hajj and Umrah are still not determined. There is limited information on antimicrobial resistance among S. pneumoniae isolated from diseased pilgrims and no information on the serotypes involved. Finally, the efficacy and effectiveness of the current vaccines in the context of Hajj and Umrah have not been studied. Research agendas proposed in this article would help fill knowledge gaps regarding pneumococcal disease at Hajj and Umrah and would constitute a strong basis for an informed and potentially unified policy regarding pneumococcal vaccination for these events.